PENDEKATAN PERSONAL DALAM MENGATASI KESULITAN BELAJAR SISWA SEKOLAH DASAR: STUDI KASUS PADA SISWA KELAS V - Regina Sipayung; Lastri Helmalia Sitohang; Ella Sharifa Tamba; Herna Elisabeth Lumbanbatu; Elisabeth Sihombing; Kurnia Devi Saragih (PT. LEMBAGA PENERBIT PENELITIAN NUSANTARA, 2025)
This study aims to determine the effectiveness of a personal approach in helping elementary school students who experience learning difficulties. The subject of the study was a fifth-grade student with the initials D, who showed obstacles in learning focus, motivation, and independence. The methods used included observation, interviews, and the provision of guidance services in two sessions. The results of the study indicate that a personalized approach can enhance self-awareness, problem-solving skills, and learning focus among students. Additionally, active support from parents and teachers plays a significant role in supporting the success of counseling. This study contributes to counseling practice in elementary schools by emphasizing the importance of empathetic and collaborative individual interventions.